(untitled) (Huellas, 2024)
The article focuses on the problem of indigenous socio-territorial conflicts related to open-pit metal mining in Argentina at the beginning of the 21st century. The analysis emerges from a qualitative doctoral research, with an anthropological approach, where the case study was addressed in a peasant-indigenous territory located in the Cangrejillos locality (Yavi - Jujuy department), in the Puna region, during the first decade of the 21st century. This indigenous community has a long history of defending and recognizing its community territory in different historical contexts. From its origin to the present, the fight for land became more complex as interests in the area changed and the possibilities of defense through legal means made it possible to make other dimensions and levels of the problem visible and enabled. Towards the beginning of the 21st century, open-pit metal mining began to advance throughout the region, a situation that alerted the community and the socio-environmental dimension was incorporated into the historic struggle to obtain community titles. The demand made by the community intensified based on the transformation of the notion of community land into territory.